ANALISIS KETERLAMBATAN PROYEK PERUMAHAN GRIYA EMAS KARANGPLOSO MENGGUNAKAN METODE CPM (CRITICHAL PATH METHOD) (Magister Teknik Sipil, Fakultas Teknik, Universitas 17 Agustus 1945 Surabaya, 2022)
The Crashing method that will be used in this research is expected to provide answers to the demands of the optimal duration of the Karangploso Griya Emas Housing development project. The objectives of this study are: 1) Determine the working network or network of Karangploso Griya Emas Housing development projects; 2) Analyzing the optimal time to complete the Karangploso Griya Emas Housing construction project; 3) Analyzing the estimated cost for the Karangploso Griya Emas Housing development project, which will accelerate its completion time. This research uses quantitative research methods, namely research methods with survey methods in the form of data collection through tests or interviews and literature studies by collecting literature in accordance with existing case studies. The information collected is in the form of: housing project specifications, schedule, RAB (Budget Plan), working drawings, number of workers, existing field conditions, number of units built and the progress of activities. The results of this study indicate that: 1) From the results of CPM analysis with the help of Microsoft Project, the work included in critical activities is Soil Galian, 1: 1: 3 River Stone Installation, Sand Foundation Urugan, Inner Soil Urugan, Bata Merah Pair 1 : 3, Plastering Aci and Wall Paint; 2) With CPM Analysis and Crashing method, 40% of workers are added which results in an optimal project duration of 37 days; 3) From the initial cost of the construction project of 1 housing unit, Rp. 37,500,000.00, the total cost obtained after the crash was Rp. 52,650,810.00 with additional costs due to crashing of Rp. 15,150,810.00.